Online Estimation of Plant Participation Factors for Automatic Generation Control in Power Systems with Variable Energy Resources; IEEE Transactions on Industry Applications; Vol. ХХ, iss. Х - Tsydenov E. A. Evgeny Aleksandrovich (2022, 2022)
Title screen